Optimal capacity of graded-response perceptrons - Bollé, Désiré; Kühn, Reimer; Van Mourik, Jort (Journal of physics. A, Mathematical and general, 1993)
Optimal capacities of perceptrons with graded input-output relations are computed within the Gardner approach (1988). The influence of desired output precision, stability with respect to input errors, and output-pattern statistics are analysed and discussed.
Gesehen am 15.06.2023
Falsche Namensform in der Verfasserangabe. Richtig: Kühn, Reimer